STUDY OF THE WORKLOAD METHOD, STAFFING NEEDS INDICATOR IN HEALTH FACILITIES: SYSTEMATIC LITERATURE REVIEW - Teguh Utama; Seftika Sari; Neni Frimayanti (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Measuring workload plays a crucial role in ensuring optimal performance, employee welfare, and efficient resource allocation. The Workload Indicator Staffing Need (WISN) method has been widely used to assess workload and workforce needs. This systematic literature review aims to evaluate the applicability, reliability, and validity of the WISN method in the context of health services. A systematic search of relevant databases (PubMed & Google Scholar) was conducted to identify studies published between 2014 and 2024, focusing on the application of the WISN method in healthcare. Adopting the PRISMA methodology, 10 articles were selected from an initial 200 articles based on their relevance and methodological quality. This study shows that the WISN method has been effectively applied in various health service contexts, such as hospitals, primary service centers, and clinics. This method offers a structured approach to determining workforce needs based on workload, thus facilitating the efficient allocation of resources. However, a number of studies have highlighted challenges related to data accuracy and the adaptability of the WISN method to various health service conditions. Therefore, the development and integrated approach to the WISN method is needed to balance with various other workload measurement methods to improve reliability and validity.